Distribution patterns of the common predatory bush-cricket Saga pedo (Pallas, 1771) (Orthoptera, Tettigoniidae) in the Asian part of its range: Real rarity or mysterious commonness - Shibkova, Ekaterina S.; Molodtsov, Vladimir V.; Childebaev, Muratbek K.; Yefremova, Oxana V.; Sergeev, Michael G. (Acta Biologica Sibirica, 2025)
The distribution patterns of the common predatory bush-cricket Saga pedo (Pallas, 1771) across the Asian part of its geographic range are revealed. It is the most widespread member of the genus and is the only species crossing the 55th parallel in the north direction. Preferable habitats of S. pedo are more or less uniform across its range, it favors variable steppe or steppe-like habitats covering by relatively dense grass vegetation with presence of forbs and especially shrubs. In the western parts of its range, the species is commonly distributed across regions with the subtropical Mediterranean and the temperate southern broadleaf forests, and its populations are mainly associated with local open landscapes. In the central and eastern parts, its distribution is different, because it is usually found over the forest-steppe, steppe and semi-desert life zones and also in the mountains of Middle Asia. The MaxEnt models produced for the contemporary period and for 2021-2040 and 2041-2060 according the Shared Socioeconomic Pathway 3-7.0 and the global climate model CNRM-ESM2-1 provide an opportunity to estimate the suitability of conditions for the species and demonstrate that, in the future, the general character of its distribution may change very significantly, especially in the southern half of the West Siberian Plain. The conservation status of S. pedo is discussed for the Asian part of its range as well.